Evaluating integrated sustainable urban development strategies: a methodological framework applied in Portugal - Medeiros, E.; van der Zwet, A. (European Planning Studies, 2019)
This paper debates the evolution and importance of the urban dimension of EU policies and in particular EU Cohesion Policy in the past three decades. It discusses the growing relevance for supporting a Urban Agenda for the EU, and the gradual adoption and implementation of Integrated Sustainable Urban Development Strategies (ISUDS), by pointing out their advantages vis-à-vis mainstream sectoral-focused policy strategies. In this light, the article proposes an evaluation framework to assess and compare ISUDS across Europe. Based on the Portuguese case-study this analysis argues that despite their limited impacts, EU financed urban programmes (URBAN, POLIS, ISUDS) contributed positively to promoting a policy integrated approach, and enhanced urban physical and social environment of deprived urban neighbourhoods. More concretely, the initial results from the recent implementation of the 103 Integrated Sustainable Urban Development Strategies reveal a gradual adoption by the urban and local authorities of more holistic and integrated urban development policy approaches to increasing policy effectiveness and efficiency.